Night Embrace - Kenyon, Sherrilyn, author 407508 (London : Piatkus, 2005)
Talon was once a Celt warrior cursed by his ancient gods. Following the murder of his sister, the dying Talon had made a deal with the goddess Artemis. He had been given one act of vengeance against the clan who betrayed him, in exchange for his soul and his eternal service as a Dark-Hunter. Talon has sworn to fight Daimons and rescue the human souls they've captured. He has never had cause to regret this choice - until he meets Sunshine Runningwolf. The unconventional Sunshine should be Talon's perfect woman. She is beautiful, sexy and isn't looking for a long-term commitment. But the more time Talon spends in her company the more he starts yearning for dreams of love and family that he buried centuries ago. But loving Sunshine would be dangerous for both of them - Talon is destined never to know peace or happiness while his enemies still seek to destroy him and everyone close to him...